Arrangement of Renal Arteries in Guinea Pig. Issue 3 (31st October 2016) - Mazensky, David; Flesarova, Slavka
ABSTRACT: The aim of this study was to describe origin, localization, and variations of renal arteries in guinea pig. The study was carried out on 26 adult guinea pigs. We prepared corrosion casts of the guinea pig arterial system. Batson's corrosion casting kit no. 17 was used as the casting medium. In 57.7% of specimens, a. renalis dextra was present as a single vessel with different level of its origin from aorta abdominalis . In 38.5% of specimens, two aa. renales dextrae were present with variable origin and arrangement. The presence of three aa. renales dextrae we found in one specimen. In 76.9% of specimens, a. renalis sinistra was present as a single vessel with different level of its origin from aorta abdominalis and variable arrangement. In 23.1% of specimens, we found two aa. renales sinistrae with variable origin and arrangement. The anatomical knowledge of the renal arteries, and its variations are of extreme importance for the surgeon that approaches the retroperitoneal region in several experiments, results of which are extrapolated in human. This is the first work dealing with the description of renal arteries arrangement in guinea pig. Anat Rec, 300:556–559, 2017. © 2016 Wiley Periodicals, Inc.